Accounting principles - Weygandt, Jerry J.; Kimmel, Paul D.; Mitchell, Jill E. (Hoboken : Wiley, 2021)
"The following Feature Story about Columbia Sportswear Company highlights the importance of having good financial information and knowing how to use it to make effective business decisions. Whatever your pursuits or occupation, the need for financial information is inescapable. You cannot earn a living, spend money, buy on credit, make an investment, or pay taxes without receiving, using, or dispensing financial information. Good decision- making depends on good information. The purpose of this chapter is to show you that accounting is the system used to provide useful financial information"--
Revised edition.
Includes index.
BBS
Karim International
Keywords: Accounting; Management